Colorectal Cancer in Individuals with Cirrhosis: A Population-Based Study Assessing Practice Patterns, Outcomes, and Predictors of Survival. - Patel, Sunil; Brennan, Kelly; Zhang, Lisa; Djerboua, Maya; Nanji, Sulaiman; Merchant, Shaila; Flemming, Jennifer (Current Oncology, 2023)
Those with cirrhosis who develop colorectal cancer (CRC) are an understudied group who may tolerate treatments poorly and are at risk of worse outcomes. This is a retrospective cohort study of 842 individuals from Ontario, Canada, with a pre-existing diagnosis of cirrhosis who underwent surgery for CRC between 2009 and 2017. Practice patterns, overall survival, and short-term morbidity and mortality were assessed. The most common cirrhosis etiology was non-alcoholic fatty liver disease (NAFLD) (52%) and alcohol-associated liver disease (29%). The model for end-stage liver disease score (MELD-Na) was available in 42% (median score of 9, IQR7-11). Preoperative radiation was used in 62% of Stage II/III rectal cancer patients, while postoperative chemotherapy was used in 42% of Stage III colon cancer patients and 38% of Stage II/III rectal cancer patients. Ninety-day mortality following surgery was 12%. Five-year overall survival was 53% (by Stages I–IV, 66%, 55%, 50%, and 11%, respectively). Those with alcohol-associated cirrhosis (HR 1.8, 95% CI 1.5–2.2) had lower survival than those with NAFLD. Those with a MELD-Na of 10+ did worse than those with a lower MELD-Na score (HR 1.9, 95% CI 1.4–2.6). This study reports poor survival in those with cirrhosis who undergo treatment for CRC. Caution should be taken when considering aggressive treatment.